Unemployment and social exclusion - Pohlan, Laura (Mannheim, 2018)
"This paper analyzes the economic and social consequences of job loss which contribute to exclusion from society based on German linked survey and administrative data. To study the causal relationship between unemployment and multiple dimensions of social marginalization, I combine inverse propensity score weighting with a difference-in-differences approach. The results suggest that job loss has particularly detrimental effects on the subjective perception of social integration, life satisfaction, the access to economic resources and mental health. Moreover, this paper shows that becoming unemployed hinders the fulfillment of psychosocial needs that are typically associated with working, such as social status and higher self-efficacy. The effects of job loss are long-lasting, growing more profound the longer the duration of unemployment and persisting following reemployment. Looking at effect heterogeneity, I find that having a partner and being highly educated reduces the negative effects of job loss."